Pendidikan Agama Islam Perspektif Gus Dur di Era Digital - ijad, (Jurnal Diskursus Islam, 2025)
The chronic disease of the dichotomy of knowledge seems to still afflict some practitioners of Islamic religious education. This has resulted in discrimination manifested as an extreme separation between "religious knowledge" and "worldly knowledge." The infection of that disease has the potential to become more severe if not treated immediately, considering the advancement of the times that does not hesitate to crush anyone who cannot compromise with the digital era. The antidote to the virus was found in the concept of integrative Islamic religious education initiated by Muslim scholars. Gus Dur became one of the prominent intellectual figures who vocally advocated for integrative Islamic education with a neo-modernist approach. This research discusses integrative Islamic religious education from the perspective of Gus Dur using the library study method, where the research is based on various literature spread across different platforms. The results of this research indicate that Gus Dur has a vision for Islamic education, which should be implemented in both formal and non-formal institutions. It must be philosophically structured in terms of curriculum and teaching materials, incorporating three aspects of knowledge: classical Islamic knowledge, traditional Nusantara knowledge, and modern knowledge. According to Gus Dur, these three aspects must collaborate harmoniously to produce a generation that possesses competence in Islamic knowledge, appreciates local culture, and can keep up with various advancements in the digital era.